PENGARUH GOOD CORPORATE GOVERNANCE, CORCORATE SOCIAL RESPONSIBILITY, DAN KINRJA KEUANGAN TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Manufaktur Sektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2018-2022) - Duha, Rinumawati; Satiman, Satiman (Postgraduate Management Journal, 2025)
This research aims to find out and obtain empirical evidence regarding the influence of Good Corporate Governance, Corporate Social Responsibility and Financial Performance on Company Value in Food and Beverage Manufacturing Companies listed on the BEI in 2018 - 2022. The dependent variable in this research is Company Value, while the variable independent in this research are Good Corporate Governance, Corporate Social Responsibility, and Financial Performance. This research is quantitative in nature and uses associative methods and data comes from company annual reports for the period 2018 - 2022 with panel data regression analysis techniques. The research results in the form of the Good Corporate Governance variable with the Independent Commissioner proxy obtained a prob value of 0.3687 with a coefficient of 0.903491 which shows that Independent Commissioners do not have a significant effect on Company Value. The Good Corporate Governance variable, which is proxied by Institutional Ownership, obtained a prob value of 0.2144 with a coefficient of -3.481297, indicating that Institutional Ownership has no significant effect on Company Value. The Corporate Social Responsibility variable obtained a prob value of 0.2831 with a coefficient of -0.411141 indicating that Corporate Social Responsibility has no significant effect on Company Value. The Financial Performance variable obtained a prob value of 0.0000 with a coefficient of 4.315947 with a positive sign, indicating that financial performance has a significant positive effect on company value.